An Effective Re Deployment of Cooperative Network(S) to Transmit in Incremental Clusters Approach - Bollarapu, Manjula Josephine; Ramakoteswara Rao, G (International Journal of Computer Sciences and Engineering, 2025)
Scheduling and broadcasting of data through network tunnels is always a big challenge in closed network topologies. Each and individual tunnel or part of network will be having its own capacity to transmit and receive the packets. Adoptive and open networks are easy to transmit the data but the challenges will occur in synchronization of data transmission among them. So clustering, tracking, log maintenance of the data transmission among the channels or tunnels and retransmission with respect energy levels and synchronization can be achieved by incremental tracking retransmission (ITR[1]) approach. Energy levels will be monitored by network monitor and assigns scheduling depends on the network capacity of the available methodologies. Here the three methodologies are 1.Memory less channels[2] , 2. Modulated channel[3], 3.Joint and uniform scheduling[4] for data transmission with respect to scheduling. Considerable throughput criteria is framed with incremental flow with our work to end up fair and best accuracy levels. This ITR method is totally unique in open networks. Here open networks means which can adopt with legacy and other adoptive open networks in tunnelling or bridge level transmission. The packet buffering and delivery is always depends on previous cluster or next cluster and chance of losing the packets. So to overcome our work is practically implemented in chunks mechanism. Totally 3 or more chunks will be framed as clusters which acts as incremental growth in transmission with respect to losing of the packets. The central frame work which works as auto deployment methodology to track the tunnels. The loss of frequency is traceable using this frame work and adopts the lost and non lost packets addresses and flushes to next level to fulfil ITR method. The practical implementation depends on asynchronous services to roll back to any level/cluster. The feasible transmission is achieved in incremental level of clusters which will get the log or track information about the data from central frame work.